A sodium titanium phosphate-coated sodium iron pyrophosphate composite material and a preparation method thereof
Patent Information
- Application Number
- CN202610937552.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-26
- Publication Date
- 2026-10-16
AI Technical Summary
然而,该技术存在以下缺陷:(1)TiO2作为电子导体,无法解决NFPP本体离子扩散动力学迟缓的核心问题;(2)钛源在烧结过程中同时发生体相掺杂和表面包覆,二者的比例和分布难以精确控制,导致批次稳定性差;(3)TiO2包覆层的厚度和均匀性难以调控,容易产生局部包覆不全或过厚的问题
[0024]This invention achieves uniform and controllable coating of sodium titanate phosphate onto the surface of sodium iron phosphate particles by pre-synthesizing sodium iron phosphate pyrophosphate precursor and sodium titanate phosphate independently, followed by mechanical mixing and secondary sintering. This solves the problems of uneven coating and uncontrollable interface caused by in-situ reactions in existing technologies. This invention utilizes the NASICON three-dimensional framework of sodium titanate phosphate to provide a rapid transport channel for sodium ions, while the carbon coating layer enhances the electronic conductivity of the matrix. The two work synergistically to significantly improve the ionic conductivity and rate performance of the composite material. Furthermore, the uniform and continuous sodium titanate phosphate coating layer acts as a physical barrier, effectively suppressing electrolyte corrosion and charge/discharge volume changes, thus enhancing structural stability.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sodium-ion battery cathode material technology, specifically relating to a sodium titanium phosphate coated sodium iron phosphate pyrophosphate composite material and its preparation method. Background Technology
[0002] With the widespread application of lithium-ion batteries in portable electronic devices, electric vehicles, and grid energy storage, new energy technologies have achieved significant breakthroughs. However, the limited availability and high cost of lithium resources have constrained the large-scale development of lithium-ion batteries. Against this backdrop, sodium-ion batteries, due to their abundant sodium resources, similar electrochemical mechanisms, and lower costs, have become an ideal alternative to lithium-ion batteries.
[0003] The development of cathode materials for sodium-ion batteries is a crucial step towards their commercialization. Among these, polyanionic materials have attracted significant attention due to their advantages such as high theoretical capacity, low cost, and environmental friendliness. In particular, sodium iron pyrophosphate (Na4Fe3(PO4)2P2O7, NFPP), as a hybrid polyanionic cathode material, exhibits excellent structural stability, good thermal stability, and a high theoretical capacity. However, the inherent electronic conductivity and sluggish sodium-ion diffusion kinetics of NFPP materials severely limit their practical applications, resulting in poor rate performance and cycle capacity decay.
[0004] To overcome the aforementioned problems, researchers have explored various modification strategies, including carbon coating, elemental doping, surface engineering, and morphology control. Among these, surface coating with fast ion conductor materials is a highly efficient strategy that combines interface protection and enhanced ion conduction. For example, Chinese patent CN115504447A discloses a method for preparing a lithium titanate-coated sodium iron pyrophosphate composite material. This method employs two rounds of microwave drying for two coating processes: carbon coating and lithium titanate coating, which improves the ionic conductivity and rate performance of the material to some extent. However, this method forms the lithium titanate coating layer through in-situ reaction of titanium and lithium sources on the material surface, making it difficult to precisely control the thickness and uniformity of the lithium titanate coating layer. Furthermore, the nucleation and growth of lithium titanate during the in-situ reaction occur simultaneously with the sintering of the matrix, leading to mutual interference and uncontrollable interfacial bonding.
[0005] Furthermore, Chinese patent CN116750741A discloses a method for preparing titanium-doped carbon-coated iron sodium pyrophosphate material. This method involves a one-step process of mixing a titanium source with a sodium source, an iron source, a phosphorus source, and a carbon source, followed by sand milling, spray drying, and inert atmosphere sintering to partially coat the titanium with carbon. 4+Doping is incorporated into the NFPP lattice, while some TiO2 is coated on the particle surface. This method improves the electronic conductivity of the material to a certain extent. However, this technique has the following drawbacks: (1) TiO2, as an electronic conductor, cannot solve the core problem of slow bulk ion diffusion kinetics in NFPP; (2) During the sintering process, the titanium source undergoes both bulk doping and surface coating, and the ratio and distribution of the two are difficult to control precisely, resulting in poor batch stability; (3) The thickness and uniformity of the TiO2 coating layer are difficult to control, which can easily lead to problems of incomplete or excessive coating in some areas.
[0006] In addition, Chinese patent CN118929616A discloses a hydrogen-doped titanium dioxide-coated sodium iron pyrophosphate composite material, which forms an H-TiO2 coating layer on the surface of NFPP through a liquid-phase in-situ hydrolysis method. This coating layer is formed by Ti... 4+ / Ti 2+ The charge flow between mixed valence states enhances electronic conductivity. However, this method still fails to address the core issue of sluggish bulk ion diffusion kinetics in NFPP, and the titanium source hydrolysis rate is difficult to control precisely, easily leading to uneven coating thickness.
[0007] Therefore, there is an urgent need to develop a modification strategy that can simultaneously improve ionic conductivity and electronic conductivity, ensure uniform and controllable coating layer, and not interfere with the matrix crystal structure. Summary of the Invention
[0008] In view of the above problems, the present invention provides a sodium titanium phosphate coated sodium iron phosphate pyrophosphate composite material and its preparation method, which simultaneously improves ionic conductivity and electronic conductivity, ensures uniform and controllable coating layer, and does not interfere with the matrix crystal structure modification strategy.
[0009] The technical solution adopted by this invention to solve its technical problem is:
[0010] The first aspect of the present invention provides a sodium titanate phosphate coated sodium iron phosphate pyrophosphate composite material, the composite material having a core-shell structure, wherein the core is sodium iron phosphate pyrophosphate and the shell is a sodium titanate phosphate coating layer having a NASICON structure, the sodium titanate phosphate coating layer coating the surface of sodium iron phosphate pyrophosphate particles, and the thickness of the sodium titanate phosphate coating layer is 20~50 nm.
[0011] The sodium titanate phosphate-coated sodium iron phosphate pyrophosphate composite material provided by this invention utilizes sodium titanate phosphate as a NASICON-type fast ion conductor, providing a three-dimensional fast migration channel for sodium ions, significantly improving the material's ionic conductivity and rate performance. The uniform and continuous sodium titanate phosphate coating layer acts as a physical barrier, inhibiting the corrosion of the sodium iron phosphate pyrophosphate matrix by the electrolyte and volume changes during charge and discharge, thereby enhancing structural stability and extending cycle life. Controlling the thickness of the sodium titanate phosphate coating layer to 20-50 nm ensures both ion transport efficiency and coating integrity.
[0012] A second aspect of the present invention provides a method for preparing the above-mentioned sodium titanium phosphate coated sodium iron phosphate pyrophosphate composite material, comprising the following steps:
[0013] (1) Preparation of sodium iron pyrophosphate precursor;
[0014] (2) Sodium titanium phosphate was prepared independently by solid-state reaction method;
[0015] (3) The sodium iron phosphate precursor obtained in step (1) and the sodium titanium phosphate obtained in step (2) are mechanically mixed at a mass ratio of 6~9:4~1, and then sintered in an inert atmosphere to obtain sodium titanium phosphate coated sodium iron phosphate composite material.
[0016] Further, the preparation method of the sodium iron pyrophosphate precursor in step (1) includes: mixing sodium source, iron source, phosphorus source and carbon source in a certain proportion, and then sequentially grinding, drying, pre-sintering and final sintering, and then crushing to obtain the precursor;
[0017] It should be noted that the "pre-sintering and final sintering" refer to: first, pre-sintering at 300~400℃ for 2~5 hours to allow the precursor to initially decompose; then, final sintering at 500~700℃ for 6~12 hours to allow the material to fully crystallize. The specific temperature and time can be optimized according to the actual raw material system.
[0018] Further, the molar ratio of the sodium source, iron source, and phosphorus source is Na∶Fe∶P=(4+x)∶(3-y)∶4, where 0<x≤0.5 and 0<y≤0.3; the amount of carbon source added is 7%~10% of the total mass of the sodium source, iron source, and phosphorus source. Specifically, the sodium source is sodium pyrophosphate; the iron source is ferric phosphate or ferrous oxalate; the phosphorus source is ferric phosphate or sodium pyrophosphate; and the carbon source is glucose or polyethylene glycol.
[0019] Further, the preparation method of sodium titanium phosphate in step (2) includes: mixing sodium carbonate, titanium dioxide, and ammonium dihydrogen phosphate in a molar ratio of Na∶Ti∶P=0.4~0.6∶2∶3, ball milling the mixture, sintering it at 600~800℃ in an inert atmosphere, and then pulverizing it after cooling to obtain sodium titanium phosphate. The ball milling rate is 400~1000 r / min, and the time is 0.5~10 h; the sintering heating rate is 1~5℃ / min, and the holding time is 4~6 h.
[0020] Further, the mechanical mixing in step (3) is ball milling or sand milling, with a mixing time of 0.5~5h and a mixing speed of 100~800r / min. Its function is to: through gentle and moderate low-energy mixing, make the sodium titanium phosphate particles uniformly dispersed and physically attached to the surface of the sodium iron phosphate pyrophosphate precursor particles, avoiding excessive particle breakage, morphological damage or impurity introduction caused by excessive speed or time, while ensuring sufficient contact between the two, providing an ideal precursor mixing state for the formation of a continuous, uniform and well-bonded coating layer in the subsequent secondary sintering process.
[0021] Furthermore, the sintering temperature of the secondary sintering in step (3) is 500~600℃, and the holding time is 3~6h. Its function is: on the one hand, to promote sufficient interfacial diffusion and chemical bonding between the sodium titanium phosphate coating layer and the sodium iron pyrophosphate matrix, forming a tight and firm core-shell structure; on the other hand, to effectively maintain the integrity of the NASICON three-dimensional skeleton of sodium titanium phosphate and the crystal structure of sodium iron pyrophosphate, avoiding adverse reactions between the two due to excessive temperature or the generation of impurity phases such as sodium iron pyrophosphate (NFPO) and sodium iron phosphate (NFP), while preventing excessive particle growth caused by excessive holding time, thereby obtaining a composite material with stable interface, high ion transport efficiency and low impurity content.
[0022] Further, after the secondary sintering in step (3), the composite material is obtained by crushing and sieving. Its function is to break up any slight agglomerates or blocky materials that may be generated during the sintering process, and to obtain composite material powder with uniform particle size and good dispersibility by sieving, so as to meet the requirements of the electrode slurry coating process for powder flowability and particle size distribution, and at the same time ensure that the sodium titanium phosphate coating layer maintains a continuous and uniform coverage in the final product, thereby ensuring the consistency of the electrochemical performance and processing stability of the composite material.
[0023] Compared with the prior art, the technical solution of this application has at least the following beneficial effects:
[0024] This invention achieves uniform and controllable coating of sodium titanate phosphate onto the surface of sodium iron phosphate particles by pre-synthesizing sodium iron phosphate pyrophosphate precursor and sodium titanate phosphate independently, followed by mechanical mixing and secondary sintering. This solves the problems of uneven coating and uncontrollable interface caused by in-situ reactions in existing technologies. This invention utilizes the NASICON three-dimensional framework of sodium titanate phosphate to provide a rapid transport channel for sodium ions, while the carbon coating layer enhances the electronic conductivity of the matrix. The two work synergistically to significantly improve the ionic conductivity and rate performance of the composite material. Furthermore, the uniform and continuous sodium titanate phosphate coating layer acts as a physical barrier, effectively suppressing electrolyte corrosion and charge / discharge volume changes, thus enhancing structural stability.
[0025] Unlike existing technologies that use titanium dioxide or lithium titanate coatings, this invention employs sodium titanate with a NASICON three-dimensional framework structure as the coating layer. This structure provides an independent, rapid migration channel for sodium ions, fundamentally improving the inherent problem of low ionic conductivity in NFPP matrices. The internal in-situ carbon coating layer enhances electronic conductivity, while the external sodium titanate coating layer enhances ionic conductivity. Together, they form a synergistic effect of an "electron-ion dual conductivity network," an effect that cannot be achieved with a single electronic conductor coating layer (such as carbon, H-TiO2, TiO2, or lithium titanate). Attached Figure Description
[0026] Figure 1 The XRD pattern of the sodium titanium phosphate coated sodium iron phosphate pyrophosphate composite material prepared in Example 1;
[0027] Figure 2 SEM image of the sodium titanium phosphate coated sodium iron phosphate pyrophosphate composite material prepared in Example 1;
[0028] Figure 3 This is a magnified XRD pattern of the Ti-doped NFPP@TiO2@C material prepared in Comparative Example 5 (refer to CN116750741A). Detailed Implementation
[0029] The present invention will be further described below with reference to the accompanying drawings and embodiments. It should be noted that, unless otherwise specified, the embodiments and technical features described in this application can be combined with each other. It should also be pointed out that, unless otherwise indicated, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. The terms "comprising" or "including" and similar words used in this invention refer to elements or objects preceding the word that encompass the elements or objects listed following the word and their equivalents, without excluding other elements or objects.
[0030] Example 1
[0031] The first aspect of this embodiment provides a sodium titanate phosphate coated sodium iron phosphate pyrophosphate composite material. The composite material has a core-shell structure, with the core being sodium iron phosphate pyrophosphate and the shell being a sodium titanate phosphate coating layer. The sodium titanate phosphate coating layer coats the surface of the sodium iron phosphate pyrophosphate particles, and the thickness of the sodium titanate phosphate coating layer is tested to be 20~30nm.
[0032] The second aspect of this embodiment provides a method for preparing the above-mentioned sodium titanium phosphate coated sodium iron phosphate pyrophosphate composite material, comprising the following steps:
[0033] (1) Sodium pyrophosphate, iron phosphate and glucose are mixed in a certain proportion, sand-milled and dried, and then sintered in stages: first, pre-sintering is carried out at 350℃ for 3h, and then final sintering is carried out at 650℃ for 8h, and then crushed to obtain sodium iron pyrophosphate (NFPP) precursor; wherein, the molar ratio of sodium source, iron source and phosphorus source is Na∶Fe∶P=4.2∶2.9∶4, and the amount of carbon source added is 8% of the total mass of sodium source, iron source and phosphorus source;
[0034] (2) Sodium carbonate, titanium dioxide and ammonium dihydrogen phosphate were mixed in a molar ratio of Na:Ti:P=0.5:2:3. After ball milling (700 r / min, 5 h), the mixture was heated to 700 °C at a heating rate of 3 °C / min in an argon atmosphere and held for 5 h for sintering. After cooling, the mixture was pulverized to obtain sodium titanium phosphate (NTP).
[0035] (3) The NFPP precursor obtained in step (1) and the NTP obtained in step (2) are ball-milled at a mass ratio of 7.5:2.5 for 3 hours and a mixing speed of 500 r / min. Then, a second sintering is carried out in an argon atmosphere at a sintering temperature of 550℃ and a holding time of 4 hours. After sintering, the mixture is naturally cooled to room temperature and then crushed and sieved to obtain sodium titanium phosphate coated sodium iron phosphate pyrophosphate composite material.
[0036] Example 2
[0037] This embodiment is basically the same as Embodiment 1, except that:
[0038] In step (1), the amount of carbon source added is 5%, and the sintering conditions are: pre-sintering 300℃ / 2h, final sintering 500℃ / 6h;
[0039] In step (2), the ball milling speed is 400 r / min, the time is 0.5 h, the heating rate is 1 ℃ / min, the sintering temperature is 600 ℃, and the holding time is 4 h;
[0040] In step (3), the NFPP:NTP mass ratio is 6:4, the ball milling time is 0.5h, the rotation speed is 100r / min, the secondary sintering temperature is 500℃, and the holding time is 3h.
[0041] The thickness of the sodium titanium phosphate coating was tested to be 10~20nm.
[0042] Example 3
[0043] This embodiment is basically the same as Embodiment 1, except that:
[0044] In step (1), the amount of carbon source added is 10%, and the sintering conditions are: pre-sintering 400℃ / 5h, final sintering 700℃ / 12h;
[0045] In step (2), the ball milling speed is 1000 r / min, the time is 10 h, the heating rate is 5 ℃ / min, the sintering temperature is 800 ℃, and the holding time is 6 h;
[0046] In step (3), the NFPP:NTP mass ratio is 8:2, the ball milling time is 5h, the rotation speed is 800r / min, the secondary sintering temperature is 600℃, and the holding time is 6h.
[0047] The thickness of the sodium titanium phosphate coating was tested to be 30~50nm.
[0048] Comparative Example 1 (sodium titanate coating ratio was too low, NFPP∶NTP=9.5∶0.5)
[0049] This comparative example is basically the same as Example 1, except that the mass ratio of sodium iron pyrophosphate precursor to sodium titanium phosphate in step (3) of Example 1 is changed to 9.5:0.5.
[0050] Comparative Example 2 (Sodium titanate coating ratio is too high, NFPP∶NTP=5∶5)
[0051] This comparative example is basically the same as Example 1, except that the mass ratio of sodium iron pyrophosphate precursor to sodium titanium phosphate in step (3) of Example 1 is changed to 5:5.
[0052] Comparative Example 3 (Titanium Dioxide Solid Phase Mixed Coating)
[0053] This comparative example is basically the same as Example 1, except that the sodium titanium phosphate (NTP) prepared in step (2) is replaced with an equal mass of commercial nano-titanium dioxide (P25, average particle size 20 nm), and the mechanical mixing and secondary sintering conditions in step (3) remain unchanged. The resulting composite material is denoted as NFPP@TiO2.
[0054] Comparative Example 4 (Refer to CN118929616A, H-TiO2 coating)
[0055] Following the method in Example 1 of CN118929616A, a hydrogen-doped titanium dioxide-coated sodium iron pyrophosphate phosphate composite material (NFPP@H-TiO2) was prepared as a comparative sample of this invention. The specific steps included:
[0056] (1) Add 0.4 mol sodium dihydrogen phosphate, 0.3 mol ferric nitrate and 0.05 mol citric acid to 1 L deionized water and stir for 3 h. Spray dry the reaction solution at 110 °C and 200 mL / h to obtain NFPP precursor. Add 0.2 g NFPP precursor and 0.2 mL 25~28 wt% ammonia water to 50 mL ethanol and ultrasonically disperse for 15 min. Add 0.2 mL tetrabutyl titanate dropwise during stirring to form solution A.
[0057] (2) Solution A was heated and stirred in an oil bath at 45°C for 12 hours to form suspension B; it was filtered, washed with ethanol, and dried to obtain the NFPP precursor coated with titanium compound.
[0058] (3) The NFPP precursor coated with titanium compound was sintered in an Ar-H2 mixed atmosphere. First, it was sintered at 300℃ for 3h, and then the temperature was raised to 550℃ for 8h to obtain NFPP@H-TiO2.
[0059] Comparative Example 5 (Refer to CN116750741A, Ti doping + TiO2 coating + carbon coating)
[0060] Ti was prepared according to the method in Example 1 of CN116750741A. 0.03 -Na4Fe3(PO4)2P2O7@TiO2@C composite material. Specifically, it includes the following steps:
[0061] (1) Weigh anhydrous sodium carbonate, ammonium dihydrogen phosphate, iron phosphate, and titanium dioxide according to the molar ratio of Na∶Fe∶P∶Ti=4∶3∶4∶0.03, and add sucrose and polyethylene glycol as a composite carbon source (the total amount of carbon source is 12% of the total mass of sodium source, iron source, and phosphorus source). Add deionized water and stir evenly to form a slurry. Grind in a sand mill at 2000r / min for 60min, and control the particle size to 300~350nm.
[0062] (2) The slurry was spray-dried at an inlet temperature of 220°C and an outlet temperature of 95°C to obtain precursor powder;
[0063] (3) The precursor powder was heated to 300℃ at 2℃ / min and kept for 2h under nitrogen atmosphere, and then heated to 500℃ at 5℃ / min and kept for 10h to obtain the control sample (Ti-NFPP@TiO2@C).
[0064] Comparative Example 6 (combining the material prepared in CN116750741A with the secondary sintering of this application)
[0065] This comparative example is basically the same as comparative example 5, except that: the Ti-NFPP@TiO2@C material prepared in comparative example 5 is mechanically mixed with sodium titanium phosphate prepared in step (2) of example 1 of this application at a mass ratio of 7.5:2.5, and then sintered at 550°C for 4 hours.
[0066] Comparative Example 7 (pure NFPP@C material, without titanium coating)
[0067] This comparative example is basically the same as Example 1, except that the sodium titanium phosphate coating in steps (2) and (3) is not performed, and only carbon-coated NFPP material (NFPP@C) is prepared. Specifically, the NFPP precursor obtained in step (1) is directly crushed and sieved to obtain the comparative sample.
[0068] Comparative Example 8 (sodium titanium phosphate coating, but without secondary sintering)
[0069] This comparative example is basically the same as Example 1, except that: only mechanical mixing is performed in step (3), and secondary sintering is not performed. That is: after mechanically mixing the NFPP precursor with sodium titanium phosphate, the comparative sample is directly obtained by crushing and sieving.
[0070] from Figure 1 As can be seen, the coating material obtained by mixing NFPP and NTP in a ratio of 7.5:2.5 has a significantly increased main phase ratio of 90.6%, and effectively suppresses the proportion of impurity phases sodium iron pyrophosphate (NFPO) and sodium iron phosphate (NFP), greatly improving the electrochemical performance of the material.
[0071] from Figure 2 As can be seen, this powder structure, characterized by a wide particle size distribution, a near-spherical main body with a small number of non-spherical particles, and a random packing state, can significantly improve the packing density through the gradation and filling effect of particles of different sizes. At the same time, the near-spherical particles can optimize flowability and processing performance, while a certain degree of surface roughness and interparticle contact can also enhance the mechanical interlocking between particles. In terms of electrical properties, high packing density can reduce porosity and lower contact resistance. The uniform and sufficient particle contact network helps to build a continuous conductive path, improve the overall conductivity and charge transport efficiency of the material, and at the same time reduce polarization loss, thereby improving the rate performance and cycle stability of the electrochemical system.
[0072] from Figure 3 As can be seen, compared with sodium titanium phosphate coating doping, the synthesized material after direct Ti doping has a significantly increased number of impurities, and its main phase peak intensity is weakened. This indicates that direct Ti doping reduces the material's performance.
[0073] As shown in Table 1, the sodium titanium phosphate coated sodium iron pyrophosphate composite materials prepared in Examples 1-3 all exhibited high charge / discharge specific capacity and high NFPP content in the main phase. Among them, Example 1 showed the best overall performance (0.1C discharge specific capacity 107.3 mAh / g, NFPP main phase content 90.6%, and NFPO and NFP impurities only 8.3% and 1.1%, respectively). Comparative Example 1 showed a slight decrease in performance due to its low coating ratio (NFPP∶NTP=9.5∶0.5), while Comparative Example 2 showed a significant decrease in capacity and purity due to its high coating ratio (5∶5). Comparative Examples 3-6 used non-NTP coatings (such as TiO2, H-Ti). None of the methods (such as O2 doping, Ti doping + TiO2 coating, etc.) could achieve the performance level of the examples. Among them, Comparative Example 3 (TiO2 solid phase mixed coating) had the worst performance with a main phase content of only 71.7% and an NFP impurity phase as high as 15.6%. Comparative Examples 4 and 5 showed some improvement but were still significantly lower than the examples. Even with the introduction of secondary sintering in Comparative Example 6, the performance was still not as good as Example 1. Although the titanium-free pure carbon coating in Comparative Example 7 had the highest initial efficiency (93.2%), the main phase purity was lower than that of Example 1. Comparative Example 8 lacked secondary sintering, resulting in ineffective bonding of the coating layer and the worst performance (discharge specific capacity of only 67.3 mAh / g, main phase of only 63.0%). The above results fully demonstrate that using the pre-synthesized sodium titanium phosphate in the specific proportion of this application for coating and combining it with the secondary sintering process can effectively suppress the formation of NFPO and NFP impurity phases and significantly improve the purity of the NFPP main phase and electrochemical performance.
[0074] Among them, the material obtained by ball milling and mixing NFPP precursor and NTP at a mass ratio of 7.5:2.5 and then sintering twice showed the lowest impurity phase and exhibited the best electrochemical performance. The mass ratio was adjusted as in Examples 2 and 3 and Comparative Examples 1 and 2. Insufficient NTP addition will result in: 1. Incomplete and uneven coating: A continuous and dense coating layer cannot be formed on the surface of NFPP particles, resulting in exposed areas and failing to fully utilize the fast ion conduction advantage of NTP; 2. Limited improvement in ion / electron conduction: It is difficult to construct a complete fast sodium ion migration channel, and the shortcomings of low electronic conductivity and slow sodium ion diffusion of NFPP itself cannot be effectively improved, resulting in poor rate performance; 3. Deteriorated impurity phase suppression effect: It cannot effectively suppress the formation of impurity phases such as NFPO and NFP, the proportion of the main phase decreases, the crystal structure stability is weak, the charge and discharge volume expansion cannot be buffered, and the cycle capacity decay is accelerated. Excessive NTP addition can lead to: 1. Decreased proportion of active material: NTP is a non-high-capacity active phase. Excessive doping will dilute the main active material of NFPP, directly resulting in a decrease in the reversible specific capacity of the material; 2. Excessive coating layer hinders ion transport: An excessively thick NTP layer will lengthen the diffusion path of sodium ions, increase migration resistance, and thus reduce the ion kinetic rate and increase polarization.
[0075] Table 1 Performance test results of different embodiments and comparative examples
[0076]
[0077] The embodiments described above are some, but not all, embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed application, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
Claims
1. A sodium titanium phosphate coated sodium iron phosphate pyrophosphate composite material, characterized in that, The composite material has a core-shell structure, with the core being sodium iron pyrophosphate and the shell being a sodium titanate coating layer with a NASICON structure. The sodium titanate coating layer coats the surface of the sodium iron pyrophosphate particles, and the thickness of the sodium titanate coating layer is 20~50nm.
2. A method for preparing the sodium titanium phosphate coated sodium iron phosphate pyrophosphate composite material as described in claim 1, characterized in that, Includes the following steps: (1) Preparation of sodium iron pyrophosphate precursor; (2) Sodium titanium phosphate was prepared independently by solid-state reaction method; (3) The sodium iron phosphate precursor obtained in step (1) and the sodium titanium phosphate obtained in step (2) are mechanically mixed at a mass ratio of 6~9:4~1, and then sintered in an inert atmosphere to obtain sodium titanium phosphate coated sodium iron phosphate composite material.
3. The preparation method according to claim 2, characterized in that, The preparation method of the sodium iron pyrophosphate precursor in step (1) includes: mixing sodium source, iron source, phosphorus source and carbon source in a certain proportion, and then sequentially grinding, drying, pre-sintering and final sintering, and then crushing to obtain the precursor.
4. The preparation method according to claim 3, characterized in that, The molar ratio of sodium source, iron source and phosphorus source is Na∶Fe∶P=(4+x)∶(3-y)∶4, where 0<x≤0.5 and 0<y≤0.3; the amount of carbon source added is 7%~10% of the total mass of sodium source, iron source and phosphorus source.
5. The preparation method according to claim 2, characterized in that, The preparation method of sodium titanium phosphate in step (2) includes: mixing sodium carbonate, titanium dioxide and ammonium dihydrogen phosphate in a molar ratio of Na∶Ti∶P=0.4~0.6∶2∶3, mixing by ball milling, sintering at 600~800℃ in an inert atmosphere, and pulverizing after cooling to obtain sodium titanium phosphate.
6. The preparation method according to claim 2, characterized in that, The mechanical mixing in step (3) is ball milling or sand milling, with a mixing time of 0.5 to 5 hours and a mixing speed of 100 to 800 r / min.
7. The preparation method according to claim 2, characterized in that, The secondary sintering temperature in step (3) is 500~600℃, and the holding time is 3~6h.
8. The preparation method according to claim 2, characterized in that, After the secondary sintering in step (3), the composite material is obtained by crushing and sieving.
Citation Information
Patent Citations
Preparation method of lithium titanate coated sodium ferric pyrophosphate composite material
CN115504447A
Preparation method and application of titanium-doped carbon-coated ferric sodium pyrophosphate material
CN116750741A
Preparation method and application of ferric sodium phosphate pyrophosphate composite material
CN118929616A